The Amulet of Samarkand / 1 - Stroud, Jonathan (Stroud, Jonathan. Bartimaeus, 2004)
Nathaniel, a young magician's apprentice, becomes caught in a web of magical espionage, murder, and rebellion, after he summons the djinni Bartimaeus and instructs him to steal the Amulet of Samarkand from the powerful magician Simon Loveland.